Synthesis, gallium-68 radiolabelling and biological evaluation of a series of triarylphosphonium-functionalized DO3A chelators - Smith,A; Blower,P; Southworth,R; Ma,M; Long,N (Dalton Transactions, 2018)
Radiolabelled lipophilic cations that accumulate in mitochondria according to the magnitude of the mitochondrial membrane potential can be used to report non-invasively on mitochondrial dysfunction in cardiovascular disease, cardiotoxicity, and cancer. While several such cations are already commercially available for SPECT imaging, PET offers greater promise in terms of sensitivity, resolution, and capacity for dynamic imaging and pharmacokinetic modelling. We have therefore synthesised a series of three triarylphosphonium-functionalised DO3A chelators for positron emitter gallium-68, with differing alkyl-functionalisation motifs to provide opportunities for tunable lipophilicity as a means of optimising their pharmacokinetics. To assess their capacity to report on mitochondrial membrane potential, we assessed their pharmacokinetic profiles in isolated tumour cells and isolated perfused rat hearts before and after mitochondrial depolarisation with the ionophore CCCP. All three compounds radiolabelled with over 97% RCY and exhibited logD values of between −3.12 and −1.81. In vitro assessment of the uptake of the radiotracers in cultured tumour cells showed a three-fold increase in uptake compared to unchelated [68Ga]Ga(III). However, each complex exhibited less than 1% retention in healthy hearts, which was not significantly diminished by mitochondrial depolarisation with CCCP. This preliminary work suggests that while this approach is promising, the lipophilicity of this class of tracers must be increased in order for them to be useful as cardiac or cancer imaging agents.